Urban energy internet: Concept and key technology - Quan Tang; Weiting Xu; Li Shen; Xi Ye; Yue Xiang; Junyong Liu; Yi Niu; Juhua Hong (2016 3rd International Conference on Systems and Informatics (ICSAI), 2016)
Urban Energy Internet is an energy ecosystem, which is based on smart distribution network, and constructed by a variety of highly coupled networks. Urban Energy Internet is an effective solution for the high penetration integration of distributed energy and improvement of energy utilization efficiency. Firstly, the development process of Urban Energy Internet is elaborated, and then the key technologies of Urban Energy Internet are extracted through the description and comparison of demonstration projects domestic and abroad. Finally, the main issues and challenges faced by Urban Energy Internet are prospected, which is in order to provide references for the researches of Urban Energy Internet.